Effectiveness of Brown Rice (Oryza Nivara) in Lowering Blood Glucose Levels in Patients with Diabetes Mellitus - Putri, Khoirunnisa Rahmania; Prasasi, Nabila Jihan; Saryono, Saryono (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
Background: Diabetes is defined as a state of hyperglycemia in either the fasting or postprandial state. The chronic hyperglycemia of diabetes mellitus (DM) is associated with organ damage, dysfunction, and failure in organs and tissues including the retina, kidney, nerves, heart, and blood vessels. Objective: This systematic review aims to study the potential of brown rice as a food substitute for white rice that can reduce blood sugar levels in patients with Diabetes Mellitus. Methods: This study is a systematic review using the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) method by searching journals in electronic databases published in PubMed, Science Direct, Scopus, and Google Scholar, published from 2013 to 2023. These articles were then extracted by looking at the titles and abstracts to see if they were relevant to the topic. Results: The 6 selected articles showed that brown rice has the potential as an additional food ingredient to reduce blood glucose levels. Brown rice contains complex carbohydrates that can control the increase in the glycemic index (GI) in the blood so that it does not increase drastically. Research results from Sulistyowati show that in addition to its high fiber content, brown rice also has a mineral content seven times higher in Magnesium and Manganese than white rice. Fiber and minerals are important components needed by people with DM as they are thought to help control blood glucose. Conclusion: Brown rice consumption can reduce blood glucose levels and thus prevent more severe diabetes mellitus.